Documentary of Woody flora and its usage in Maruthamalai Hills of the Southern Western Ghats of Coimbatore district, India - Sarvalingam, A.; Rajendran, A.; Sivalingam, R (Research in Plant Biology, 2011)
The present study described the occurrence of woody species and its usage inMaruthamalai Hills of the southern Western Ghats. A total of 119 species were collected ofwhich one individual categorized as gymnosperm and the remaining 118 individualscategorized as an angiosperms. Among the life habit the trees are the dominant species (86)other than shrubs (28) and lianas (5). The Fabaceae, Mimosaceae, Caesalpiniaceae andBignoniaceae are the dominant families of woody flora of the Maruthamalai Hills. Theimportance of recording the usage of plants in this region is imperative because of rapid lossof forest wealth and traditional wisdom. In view of the various resources use, habitatuniqueness and anthropological pressure on the forest resources, the need for conservation isstressed.